Analisis asam oksalat pada pembuatan asam sunti (Averrhoa bilimbi) berdasarkan variasi konsentrasi garam dan suhu pengeringan - Lenny Amelia HK; Kelik Putranto (Composite : Jurnal Ilmu Pertanian, 2025)
Bilimbi (Averrhoa bilimbi) is a popular raw material in the production of asam sunti, known for its distinct sour taste. Oxalic acid, which is found in bilimbi, can affect the quality and safety of the final product. Asam sunti is a fermented product that involves a preservation process using salt, which not only adds flavor but also has the potential to alter the nutritional content of the raw material. This study aims to analyze the oxalic acid content in the production of asam sunti from bilimbi (Averrhoa bilimbi) with variations in salt concentration and drying temperature. The study uses an experimental method with variations in salt concentration (5%, 10%, and 15%) and drying temperature (40°C, 50°C, and 60°C) to determine their effects on the oxalic acid content. The results show that both salt concentration and drying temperature affect the oxalic acid content in asam sunti. The treatment with 15% salt concentration (a3) and 40°C drying temperature (b1) gave the best results because these two factors support each other in maintaining the oxalic acid content. The 15% salt concentration is high enough to improve preservation and drying, while the 40°C drying temperature is optimal for preventing the degradation of chemical components.